2019
DOI: 10.1111/cid.12826
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing marginal bone loss at a hydrophilic implant design placed with or without GBR procedures: A 5‐year retrospective study

Abstract: Background Ongoing marginal bone loss is a threat to the longevity of implant‐supported prostheses. Aim The aim of the present study was to retrospectively evaluate the survival rate and factors affecting marginal bone levels at a hydrophilic implant design after 5 years in function. Materials and Methods The study group consisted of 51 consecutive patients previously treated with 159 hydrophilic implants (Neoss Straight Proactive implants) and scheduled for annual check‐ups with clinical and radiographic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…After one year of follow-up, AS implants had less bone loss and remodeling (BLC = −0.27 ± 0.40 mm). This result is similar to The highest remodeling rate occurred in the first 3 months, before occlusal loading, as already evidenced in previous studies (Donos et al, 2018;Zumstein et al, 2019). Although there was no statistically significant difference between the groups, the hydrophilic surface showed better CBL and BLC values, consistent with those in the literature (Lang et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After one year of follow-up, AS implants had less bone loss and remodeling (BLC = −0.27 ± 0.40 mm). This result is similar to The highest remodeling rate occurred in the first 3 months, before occlusal loading, as already evidenced in previous studies (Donos et al, 2018;Zumstein et al, 2019). Although there was no statistically significant difference between the groups, the hydrophilic surface showed better CBL and BLC values, consistent with those in the literature (Lang et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Implants with surface treatments capable of improving bone-implant interactions, protein adsorption, adhesion, differentiation, and cell proliferation have been used in cases with impaired bone beds (Boyan et al, 2017;Khandelwal et al, 2013;Nack et al, 2015). Implants with hydrophilic surfaces have shown promising results in clinical studies with patients using anticoagulants (Marković et al, 2017), diabetic patients (Khandelwal et al, 2013), patients with a history of radiotherapy in the head and neck region (Nack et al, 2015), patients requiring bone grafting (Donos et al, 2018(Donos et al, , 2019Marković et al, 2016;Nedir et al, 2013;Yu et al, 2017;Zumstein et al, 2019), and patients undergoing rehabilitation of the posterior maxillary (Novellino et al, 2017) and mandibular regions (Velloso et al, 2019). To date, clinical studies involving SLActive hydrophilic surfaces in mandibular implant overdenture treatment (Al-Nawas et al, 2012;Müller et al, 2015;Quirynen et al, 2015;Reis et al, 2019;Stoker & Wismeijer, 2011) have observed 1-year survival rates of 97.8% (Al-Nawas et al, 2012) to 100% (Reis et al, 2019), 98% (Stoker & Wismeijer, 2011) after 40 months, and 97.8% to 98.9% after 5 years (Müller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only one implant was lost after 4 years of prosthetic loading, while the remaining 35 implants showed no problems, giving a survival rate of 97.2% after 5 to 13 years. The mean bone loss was 1.0 ± 0.4 mm at follow-up, which is similar to those found in previous studies on the same implant design and followed for at least 5 years [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…2,3 There is already considerable evidence that the survival and success rates of implants placed in GBR sites are comparable to those of implants placed in the pristine bone, [4][5][6] and the implant survival rates range from 95% to 100% within 5 years at both GBR and pristine sites. [5][6][7][8] Systematic reviews of the literature have also shown that implants placed with staged or simultaneous GBR procedure can achieve high survival and success rates. [9][10][11] Simultaneous GBR Implants placed in a bone augmentation area have been reported…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of implants placed with simultaneous GBR procedures has rarely been reported, 1,14,15 and even fewer studies have analyzed the risk factors for implant loss. 8,16 Drawing reliable conclusions is challenging because of the limited number of patients and the wide variety of grafting materials and barrier membranes used alone or in combination. 17 The objective of this study was to assess the survival rate of implants placed simultaneously with GBR and to analyze the risk factors for implant loss.…”
Section: Introductionmentioning
confidence: 99%